Perception of barriers to physical exercise in women population over 60 - Jéssica Bianca Aily; Letícia Carnaz; Ana Claudia Silva Farche; Anielle Cristhine de Medeiros Takahashi (Universidade Estadual Paulista (UNESP), 2017)
Abstract Aims This study evaluated the possible barriers to the permanence of physical exercise (PE) of old women. Methods The study population comprised 61 old women participants for at least one year of a supervised PE program, who underwent anamnesis, and applied the Barriers Questionnaire to Physical Activity Practice in the Elderly (QBPAFI). Exploratory factorial analysis was used to evaluate QBPAFI data. The analysis of principal component was applied to the 22 questions through orthogonal rotation to analyze the correlation between the questions. The Kaiser-Meyer-Olkin test was applied to evaluate the suitability of the sample size, and the Bartlett's test to assess whether the original matrix correlation is an identity matrix. Eigenvalues greater than 1 were considered for analysis. Results The motivational factor was the major determinant of perceived barriers (43.3%), followed by psychosocial (12.29%), facilities and appearance (8.75%), and exercise conditions (8.10%) factors. Conclusion Knowing the benefits of physical activity, and the main barriers that prevent the permanence of active old people to physical exercise programs, new strategies must be taken to increase the rate of adherence of this group.